A theology for the earth : the contributions of Thomas Berry and Bernard Lonergan - Dalton, Anne-Marie (Religions and beliefs series, 1999)
While many feel that something must be done, few perceive the state of the ecological crisis as a "profound religious problem." While Thomas Berry sought to fire the imagination and motivate his listener to action, Bernard Lonergan was absorbed by the growing gulf between traditional Christian theology and its relevance to modern problems. This book brings together the work of these dynamic thinkers and examines their mutual contribution to theology for our time and for our planet.